Perlindungan Hukum Terhadap Perempuan Korban Revenge Porn Melalui Konten Pornografi Yang Dibuat Berdasarkan Kesepakatan (Based On Consent) - Mufidatul Ma'sumah; Halimatus Khalidawati Salmah; Bellinda Oktovani BP (Fakultas Hukum, Universitas Boyolali, 2024)
Social media, which is increasingly being used nowadays, has also increased cases of sexual violence, namely online gender-based violence (KBGO). In 2022, there will be 1,721 cases. Revenge porn is widespread and experienced by women. As victims, women often receive negative treatment from society or their families. The shame of the victim's family in reporting and the lack of understanding of law enforcement also make it difficult for victims to defend themselves before the law, especially in revenge porn based on consent. The formulation of this research problem is: How does positive law in Indonesia provide legal protection for women as victims of revenge porn? Is revenge porn carried out based on an agreement (based on consent) included in the type of crime of sexual violence? The normative judicial method was carried out based on the findings of secondary and primary data from the team on victims, perpetrators, witnesses, officials of the Women's and/or Children's Protection Service of Malang City/Regency, and experts. Analyzed using qualitative descriptive methods. Produce: First, Indonesia already has Republic of Indonesia Law No. 13 of 2006 in conjunction with Republic of Indonesia Law No. 31 of 2014 concerning Witness and Victim Protection Institutions and Republic of Indonesia Law, UU Pornografi, UU ITE, No. 12 of 2022 concerning Criminal Sexual Violence as a form of legal protection for women victims of revenge porn. Second, the action of revenge porn based on consent fulfills the elements in Article 14 of Republic of Indonesia Law No. 12 of 2022 concerning the crime of sexual violence.